Re-Imagining Post COVID Education the Challenges and Opportunities of Blended Approaches in Bangladesh (American Journal of Multidisciplinary Research and Innovation, 2023)
The COVID-19 epidemic has taught the global education community, including Bangladesh. After the epidemic, switching to online education was very difficult. Many educational institutions worldwide struggled to switch from on-campus to online learning since it required considerable adjustments to their digital competences, pedagogical expertise, psychosocial counseling, interaction levels, engagement techniques, evaluation methodologies, support systems, etc. After the Covid period, should we return to traditional teaching and learning approaches or embrace the revolutionary new possibilities? Never. What tactics should we use? For this study, Bangabandhu Digital University, Bangladesh Open University, and Daffodil International University researchers gave students and instructors a semi-structured questionnaire. Blended learning is common in Bangladesh, according to preliminary study. We identified numerous challenges and potential for building a sustainable blended education system in Bangladesh using the Blended Education For All (BEFA) model.